Implementation of Crime Prevention Throuh Environmental Design (CPTED) in Manado oldy city center area (ARTEKS : Jurnal Teknik Arsitektur, 2024)
North Sulawesi Province has the third highest crime rate in Indonesia in 2020 based on BPS data on 2021 crime statistics. This study chose locations in the old downtown area which has a high vulnerability to crime using the Crime Prevention Through Environmental Design (CPTED) approach. which is an effort to prevent crime through physical environmental design with 3 main aspects of territoriality, surveillance, access control which aims to minimize crime, especially in public spaces, through several stages of implementation, including knowing how far the CPTED concept is realized by using Pearson correlation analysis between the realization of CPTED and the level of The crime is based on visitors' security perceptions using questionnaire data and will then be implemented in the form of a design visualization of the old downtown area of Manado. The results of the research show that the surveillance aspect has the highest manifestation and the correlation between the three CPTED aspects has a relationship with visitors' security perceptions, and the strongest relationship is between surveillance and visitor’s security perceptions, then the implementation of area design is more dominant in open environmental designs. Based on these results, they were then implemented in the design of the old downtown area which has a strong local image and identity in corridor areas and access in public spaces.
Keywords: Crime; CPTED; Old downtown district of Manado; Perception of safety